Price Responsiveness of Marketed Surplus of Wheat in Pakistan (The Pakistan Development Review, 1974)
The crucial role of the marketed surplus of food grains in the process of development has been generally recognized. Knowledge of the determinants of the marketed quantities of food is essential for designing price and tax policies for the agricultural sector. This knowledge is required for estimating the food availability for the urban sector and for forecasting the required level of food-grains imports in any one year. In the case of crops which are wholly or almost wholly marketed the elasticities of output and market supply can be regarded as approximately equal. But in the case of crops a substantial part of whose output is retained by peasants for self consumption, the responsiveness of the marketed surplus must be meas¬ured separately from the responsiveness of output. Food crops in Pakistan constitute a major part of farm production and almost sixty per cent of grain output is. consumed by farm families themselves. In this paper, some estimates of the price elasticity of market supply for the major food crop in Pakistan are generated. Implications for food grains price policy are then drawn.